Review of clinical predictors of haemorrhagic and ischaemic stroke in Emergency Department, HKL : an observational study - Abidin, Zainal Effendy Zainal (2006)
The emergence of reperfusion therapy in acute ischemic stroke has revolutionized the management of an acute ischemic stroke. However, this approach have been hampered by lack of urgency from the patients itself, public and medical personnels. These were probably due to lack of knowledge in current management from all involved. Aim of this study is to review common signs and symptoms in stroke and to see if we can safely differentiate between types of stroke. This study also wants to look at time taken by each patient to arrive at Emergency Department. METHOD: A cross-sectional observational study for all clinically diagnosed stroke patients admitted to Hospital Kuala Lumpur from January to May 2005 after fulfilling the inclusion and exclusion criteria. All patients were subjected to brain Computed Tomography. Common signs and symptoms on admission that were reviewed are: Age, sex, ethnic, Glasgow Coma Scale, Systolic and Diastolic blood pressure, loss of consciousness, headache and vomiting. RESULTS: A total of one hundred and forty-three (Eighty-eight male and fifty-five female) patients were included in this study. Sixty-four point three percent of patients presented to Emergency Department six hours after the initial symptoms started with majority of them are ischemic stroke patients. Haemorrhagic stroke patients are more likely to be younger (mean age of fifty-one years versus fifty-six years), to have symptoms of loss of consciousness (twenty-three point one percent: p value less than 0.001), headache (Eighteen point two percent: p value less than 0.001) and vomiting (nine point eight: pvalue less than 0.001), and lower Glasgow Coma Scale (mean=9, Standard Deviation=2.8) and higher Systolic blood pressure (mean=174.77, Standard Deviation=22.5). CONCLUSION: Significant predictors for stroke patients to have higher probability of haemorrhagic type are lower age group, presented with loss of consciousness, headache and vomiting, and have lower Glasgow Coma Scale and higher Systolic blood pressure. Ischemic stroke patients are more likely to present late, more than six hours to Emergency Department while Haemorrbagic stroke patients are more likely to present earlier, within three to six hours.